“I’m Just Not Good at Math!” Rethinking What You Know About Mathematics (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
There are many misconceptions regarding mathematics that produce negative student dispositions in a classroom. Such misconceptions are not fact based but are due to an ineffective, fixed mindset where a student limits their abilities based upon low self-efficacy and self-concept. Fixed mindsets fuel negative attitudes toward mathematics and can contribute to math anxiety. Studies have shown that the brain can grow and develop throughout a person’s life is partially dependent upon one’s mindset and experiences. Mathematics teachers can utilize a growth mindset where students have high self-efficacy and self-concept to promote positive dispositions toward mathematics. In doing this, teachers must model high teacher efficacy themselves and believe in student ability by disregarding false limitations set by prior experiences.